Rancang Bangun Sistem Informasi Tugas Akhir Pada Fakultas Teknik Universitas Wijaya Putra Surabaya - Doni, Dona; Sunarto, Dewiyani; Nurchyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Engineering Faculty of Wijaya Putra Surabaya University in every semesterÂ  hold a final project test. The purpose of this activity as a condition of a student to earn an engineering degree. The process of implementation of the final project in the faculty of engineering experience some obstacles, such as: (1) determination lecturers examiners, (2) final project scheduling, and (3) delivery final project schedule. Some obstacles arise due, because there is no system that can integrate every department, which involved in the implementation of final project. Based on the identification of problems, then it is necessary to design analysis needs stakeholders, to build a web-based information system, which capable of integrating every department. Information systems are built is expected to: (1) to map and recommend areas of expertise lecturer with the theme of final test materials effectively and efficiently, (2) the system is able to perform automatic scheduling based on the schedule of lecturer teaching and academic calendar schedule, and (3) the system is able to publish a schedule to all stakeholders who require. The conclusion from this study, generate design information systems that can reduce obstacles, in implementation a final project test at Engineering Faculty of Wijaya Putra Surabaya University.